Adult Education Research in Poland and Germany on the European Level: Two Sleeping Beauties? - Bernd Käpplinger (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
This paper analyzes Polish and German papers contributed to conferences of the European research society ESREA. The method "program analysis" is used. The analysis demonstrates that Polish and German researchers are present in this European forum for research in adult education. But there are also some shortcomings. Perspectives for further improvement are suggested and discussed.